Population‐based outcome analysis of diffuse large B‐cell lymphoma in people living with HIV infection and competent individuals. Issue 5 (16th August 2018) - Conconi, Annarita; Zucca, Emanuele; Margiotta‐Casaluci, Gloria; Darling, Katharine; Hasse, Barbara; Battegay, Manuel; Staehelin, Cornelia; Novak, Urban; Schmid, Patrick; Scherrer, Alexandra; Dirnhofer, Stephan; Kwee, Ivo; et al.
Abstract: The prognostic factors and outcome of 58 acquired immunodeficiency syndrome‐related diffuse large B‐cell lymphoma (AR‐DLBCL) patients from the Swiss HIV Cohort Study, diagnosed from 2004 to 2011, were compared with those of 326 immunocompetent (IC)‐DLBCL from the Hematology Division of the Amedeo Avogadro University (Italy) and the Oncology Institute of Southern Switzerland. Median follow‐up was 6 years; 5‐year overall survival (OS) was 68% (95% CI: 63%‐73%) in IC‐DLBCL and 63% (95% CI: 49%‐75%) in AR‐DLBCL ( P = .220). The acquired immunodeficiency syndrome‐related lymphoma international prognostic index predicted OS in AR‐DLBCL. Among 148 patients younger than 61 years (40 AR‐DLBCL and 108 IC‐DLBCL) treated with RCHOP/RCHOP‐like regimens, 20 IC‐DLBCL and 9 AR‐DLBCL patients died and OS was not significantly different. A higher proportion of early deaths occurred in the AR‐DLBCL: indeed, 1‐year OS was 94% (95% CI: 87%‐97%) in IC‐DLBCL and 82% (95% CI: 66%‐91%) in AR‐DLBCL patients. After rituximab and active antiretroviral therapy introduction, AR‐DLBCL and IC‐DLBCL patients treated with curative intent have similar long‐term survival.